Effect of Tetramethylammonium Hydroxide on Nucleation, Surface Modification and Growth of Magnetic Nanoparticles. (1st August 2012) - Andrade, Ângela L.; Fabris, José D.; Ardisson, José D.; Valente, Manuel A.; Ferreira, José M. F.
Abstract : Nanoparticles of magnetite (Fe3 O4 ) were obtained by reacting ferric chloride with sodium sulphite, through the reduction-precipitation method. The effects of adding tetramethylammonium hydroxide (TMAOH) during or after the precipitation of the iron oxide were studied in an attempt to obtain well-dispersed magnetite nanoparticles. Accordingly, the following experimental conditions were tested: (i) precipitation in absence of TMAOH (sample Mt), (ii) the same as (i) after peptizing with TMAOH (Mt1), (iii) TMAOH added to the reaction mixture during the precipitation of magnetite (Mt2). Analyses with transmission electron microscopy (TEM), X-ray diffraction, Mössbauer spectroscopy, attenuated total reflectance Fourier transform infrared spectroscopy (ATR-FTIR), zeta potential, and magnetization measurements up to 2.5 T revealed that magnetite was normally formed also in the medium containing TMAOH. The degree of particles agglomeration was monitored with laser diffraction and technique and inspection of TEM images. The relative contributions of Néel and Brownian relaxations on the magnetic heat dissipation were studied by investigating the ability of suspensions of these magnetite nanoparticles to release heat in aqueous and in hydrogel media. Based on ATR-FTIR and zeta potential data, it is suggested that the surfaces of the synthesized magnetite particles treated with TMAOH become coated with (CH3 )4 N + cations.